2021
DOI: 10.1007/s10157-021-02128-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for donation after circulatory death kidney transplantation in Japan

Abstract: Background In Japan, donations after circulatory death kidney transplantation are widely performed due to legislation delays. The number of donations after brain death kidney transplantations is increasing, but the target remains unmet. We reviewed the outcomes of donation after circulatory death in Japan. Methods We analyzed 2923 deceased kidney transplantations (2239: donation after circulatory death (DCD), 684: donation after brain death (DBD)) performed in Japan from 2000 to 2019. The outcomes of the DCD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Studies have shown that donor age affects the e ciency of donation. Donors older than 50 have lower organ utilization and lower survival rate of transplanted organs [4,5]. This may be because elderly donors may be accompanied by cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that donor age affects the e ciency of donation. Donors older than 50 have lower organ utilization and lower survival rate of transplanted organs [4,5]. This may be because elderly donors may be accompanied by cardiovascular and cerebrovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, 144,302 organ transplants were completed worldwide (11.3% increase over 2020). In 2021, China has completed 19,386 organ transplants, ranking as one of the world's four major organ transplant countries with the United States (42,217), Brazil (7,088) and Spain (4,781). Organ transplants in these four countries accounts for more than 50% of the world [1].…”
Section: Introductionmentioning
confidence: 99%
“…Until the law on organ transplantation from brain-dead donors was enacted in 1997, there was no legislation for organ donation from brain-dead donors in Japan, so less than 200 cases of kidney transplantation from less than 100 donors after cardiac arrest were performed [ 21 , 22 ]. In this era, the Tokyo Women’s Medical University Group performed 11 cases of pancreas transplantation from donors after cardiac arrest [ 23 , 24 ].…”
Section: Pancreas Transplantation In Japanmentioning
confidence: 99%
“…The development of immunosuppressant therapies has greatly improved organ and recipient survival (3)(4)(5). However, acute rejection (AR) and delayed graft function (DGF) remain treatment obstacles that impair KTx outcomes, especially in the current era of donation after circulatory death (DCD) (6,7). Induction therapy, based on the conventional triple maintenance immunosuppressive therapy, can reduce the incidence of postoperative AR and DGF, allow for reduced immunosuppressant doses, and prolong transplanted kidney and recipient survival (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%